A study of hybrid nano Ag-MgO-H2O flow fluid past a slim needle with thermal radiation and Neild's boundary - G. Dharmaiah; B. Shankar Goud; Kottakkaran Sooppy Nisar; Y. Dharmendar Reddy (Case Studies in Thermal Engineering)
Numerous industrial applications depend on heat transmission processes. Hybrid nanofluids with a greater thermal exponent improve the heat transfer ability of regular fluids. A hybrid nanofluid Ag-MgO-H2O has been examined on a moving needle to assess magnetohydrodynamics, Brownian motion, thermophoresis, and thermal radiation effects. The dimensionless ordinary differential equations have been converted from partial differential equations monitoring the fluid flow model using appropriate similarity transformations. Matlab software was used to analyze the transformed equations and calculate numerical solutions. Nield's boundary condition is also considered. A first-order ordinary differential equation system is formed by transforming the partial differential equations originally generated. The present study investigates the effects of changing MHD and thermophoresis values on concentrations, temperatures, and velocity profiles. Local Sherwood number, skin friction, and Nusselt number are all assessed in the research. As well as heat transfer enhancements, energy conversion systems, advanced manufacturing, and material processing, these results have practical applications in diverse fields. Thermal systems can benefit greatly from the results to improve energy efficiency. Emerging parameters include: the mass of nanoparticles (0–40 g), the mass of the base fluid (100 g), the needle size (0.001–0.2), the radiation parameter, the magnetic field parameter, the Prandtl number, and the velocity ratio parameter. As enhancing the values of ‘c’, the result in momentum and solutal boundaries diminishes, and also reverse trend is observed on the thermal boundary. The velocity ratio factor enhances, the outcome of the velocity profile upsurges.